Guidelines Creating the Entrepreneurial Motivation of Generation Z - Chuenrenu, Theeraphat; Suttapong, Ketsaraporn (Executive Journal, 2025)
The creation of entrepreneurial motivation is a crucial factor in driving Generation Z to become more successful entrepreneurs. This academic article reviews both internal and external motivational factors, which encompasses theoretical knowledge of relevant motivation theories that influence the entrepreneurial behavior of Generation Z. It also explores strategies for fostering entrepreneurial motivation in younger generations, aiming to spark interest in entrepreneurship and help them achieve their business goals. The article proposes various approaches to enhance entrepreneurial motivation, such as support from educational institutions, collaboration between the public and private sectors, and encouragement from family and social networks. These supportive factors contribute to nurturing entrepreneurship among the younger generation, fostering entrepreneurial motivation for future generations.